Blockchain Integration for Enhanced Supply Chain Security and Transparency - Mohammad Annas; Ninda Luftiani; Qurotul Aini; Rizky Fredrin Terizla (Universitas Raharja, 2024)
In the modern global economy, the complex system of international supply chains plays a crucial role in enabling the transportation of goods and services across large geographical areas. Nevertheless, this intricate system has numerous security issues that jeopardize its smooth functioning. The risks connected with worldwide product and service distribution have been heightened due to geopolitical uncertainties, climate change-related disruptions, and the growing prevalence of cyber threats. These difficulties highlight the urgent requirement for creative solutions to protect the reliability of supply networks and guarantee continuous operations. Blockchain technology is recognized for its strong data protection features, cryptographic encryption, decentralization, and smart contract execution. It provides improved security and transparency. Concrete illustrations showcase the potential advantages of supply chain management, despite the presence of obstacles in its implementation and concerns about its long-term viability. This necessitates continuous research and cooperation to redefine the future of supply chain management.